Identifying Hierarchically Triple Star Systems with Gaia DR3 and LAMOST - Tongyu He; Jiao Li; Jiangdan Li; Jianping Xiong; Xiaobin Zhang; Mikhail Kovalev; Qiyuan Cheng; Sufen Guo; Mingkuan Yang; Xuefei Chen; Zhanwen Han (The Astronomical Journal)
Triple star systems are critical for understanding stellar dynamics and compact objects in astrophysics, yet confirmed hierarchical triples identified via spectroscopy remain limited. In this study, we identified 23 triple systems by cross matching the Gaia DR3 non-single-star catalog with Large Sky Area Multi-Object Fiber Spectroscopic Telescope DR10 spectroscopic data, 18 of them are new discoveries. For two well-observed triples, we performed radial velocity curve fitting and light curve analysis to determine their orbital parameters, with inner and outer periods of 1.26 and 656 days for one triple, and 3.42 and 422 days for the other. And we compared the results with other studies. We also analyzed the radial velocities of these 23 tripls, revealing a range of Δ V from approximately 40–210 km s ^−1 . Due to spectral resolution and detection limitations, velocity differences below 45 km s ^−1 in binaries and below 90 km s ^−1 in the inner binaries of triple systems are challenging to detect. Consequently, our detection range for inner orbital periods is restricted to 0.2–20 days, with the highest efficiency for periods under 10 days. These findings underscore the advantage of spectroscopic observations for identifying triple systems with short inner orbital periods.